‘It’s such a blackbox function’: Norwegian academic librarians’ ambivalent perceptions towards AI use in academic libraries and academia - Idunn Bøyum; Mahmood Khosrowjerdi (Information Research: An International Electronic Journal)
Introduction. In this study we report on the perceptions of Norwegian academic librarians towards the emergent role of AI in academic libraries, both in service delivery and library operations.